Analisis Perilaku Perundungan dalam Meningkatkan Percaya Diri Siswa Kelas Tinggi SDN Banjarsari 2 - ., Widya Trisna Rahayuningdiah; ., Ribut Prastiwi Sriwijayanti; ., Ryzca Siti Qomariyah (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This research was motivated by bullying behavior found at SDN Banjarsari 2 Probolinggo Regency, which had an impact on the victim's self-confidence. Based on observations, there are some students who lack self-confidence due to frequent bullying behavior carried out by their own friends. The purpose of this study was to know and analyze bullying behavior in increasing the self-confidence of high grade students of SDN Banjarsari 2. This study used descriptive qualitative method. Data collection techniques used by researchers are wawamcara, obseravsi, and documentation. The results of this study show that there are two types of bullying behavior, namely physical and non-physical bullying. Physical abuse such as hitting, kicking, choking, and pushing. While non-physical bullying such as making fun, mocking, and calling by parents' names. The psychological impact caused to the victim includes heartache, feeling afraid, inferior, and not confident.